The sociological importance of a Malay Christian subculture. - Nur Liyanah Ali Mohamed. (2009)
As a result of personal and structural factors present in Singapore, the Malay Bible study group has becomes a socially significant subculture. This thesis examines how, when, and why the Malay Bible study group becomes a place where this particular group Malay Christian converts construct their Malay Christian identity; examines how, when, and why the Malay Bible study group acts as a substitute family for a particular group of Malay converts; examines how, when, and why the Malay Bible study group is a place where this particular group of Malay Christian converts can practice Malay cultural traditions; and examines how, when, and why the Malay Bible study group is a place where this particular group of Malay Christian converts get to know other Malay Christians, with conclusions that can be generalized to other Malay Christians. I end by looking at how the data can be generalized to other religious converts.